Evaluasi Penerapan Sistem Layanan Administrasi Kependudukan Daring (Slamdung) pada Disdukcapil Kabupaten Lampung Tengah - Febriana, Dwi Febriana; Fitri Meutia, Intan; Mulyana, Nana (Journal of Governance Innovation, 2025)
This research is motivated by the innovation of the Online Population Administration Service System (Slamdung) by the Population and Civil Registration Office (Disdukcapil) of Central Lampung Regency. The purpose of the research is to evaluate the application of Slamdung and identify inhibiting factors in population services through the application. The research method used is qualitative with a descriptive approach. Data was collected using observation, interviews, and documentation. The Servqual model from Zeithalm, Parasuraman, and Berry (1990) was used as an evaluation tool for this study. The results of the study show that the implementation of Slamdung has been quite good and has brought changes in population administration services in Central Lampung Regency. However, in its implementation, there are several inhibiting factors such as the network (server) system that is not managed independently by the Central Lampung Regency Disdukcapil, the lack of socialization of Slamdung, especially after the Covid-19 pandemic, the potential to facilitate the practice of dealing with population documents, and the preference of the people of Central Lampung Regency who prefer direct population services in the office.